1986
DOI: 10.1016/0014-5793(86)80261-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activators catalyse conversion of inhibitor from fibrosarcoma cells to an inactive form with a lower apparent molecular mass

Abstract: Purified N 54 kDa plasminogen activator inhibitor from human fibrosarcoma cells was converted to an inactive form with slightly higher electrophoretic mobility by incubation with catalytic amounts of urokinasetype or tissue-type plasminogen activator. Serine proteinase inhibitors and a monoclonal antibody against urokinase-type plasminogen activator inhibited the conversion, indicating that it was caused by plasminogen activator-catalyzed proteolysis. These findings represent the first demonstration of a well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…The same result was obtained for the PAI-1 of fibrosarcoma cells [35]. However the N-terminal valine predicted from the cDNA sequence of the endothelial PAI-1 [32,33] has been confirmed by amino acid sequencing [32].…”
Section: Preparationsupporting
confidence: 63%
“…The same result was obtained for the PAI-1 of fibrosarcoma cells [35]. However the N-terminal valine predicted from the cDNA sequence of the endothelial PAI-1 [32,33] has been confirmed by amino acid sequencing [32].…”
Section: Preparationsupporting
confidence: 63%
“…N-terminal sequence analysis was performed after the incubations. At both temperatures, we found the two original N-terminal sequences of PAI-1, SAVHHPP-and VHHPPSY-, differing by the two N-terminal amino acids (Andreasen et al, 1986a). One new N-terminal sequence, MAPEEII-, appeared after incubation at O"C, but not at 37°C.…”
Section: Inhibitory Activity Of Pai-1 At Different Temperaturesmentioning
confidence: 76%
“…To produce human PAI-1 in a baculo-virus expression system, full-length human PAI-1 cDNA (a 2.2-kb fragment; Andreasen et al, 1986a) was cloned into the BurnHT site of the baculo-virus transfer vector pVLl392. Spodoptoru frugiperda cells (SF9 cells, from American Type Culture Collection, Rockville MD) were grown in BaculoGoldTM protein-free insect medium (Pharmingen, San Diego CA) supplemented with antibiotics (100 IU/ml penicillin and 50 pg/ml streptomycin; (Gibco).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAI-1 is able to inhibit u-PA activity and tumour cell invasion in an in vitro system (Nielsen et al, 1986;Cajot et al, 1990;Cubellis et al, 1990), but the practical action of PAI-I in vivo, especially in cancer cell invasion and metastasis, has remained obscure. Bouchet et al (1994) confirmed the poor prognosis of breast cancer patients whose tumours contained a large amount of PAl-1.…”
Section: Discussionmentioning
confidence: 99%